Assessing nanocrystalline pulsed transformer core performance using Maxwell ANSYS - D. Wright; K. Kelp; T. Klein; J. Stephens; J. Dickens; J. Mankowski; Z. C. Shaw; A. Neuber (AIP Advances, 2025)
This paper employs the commercial simulation software ANSYS Maxwell to explore the fast-rise short-pulse magnetic properties of Finemet nanocrystalline cores, specifically FT-3KL and FT-3KM, under high magnetization rates (>0.5 T/μs) in pulsed power applications. This study aims to leverage ANSYS’s modeling capability to simulate core behavior under high magnetization rates by comparing the simulations’ saturation characteristics and B–H curve responses with experimental results. A custom solid-state pulse generator excites the cores with quasi-square pulses, featuring ∼20 ns rise time and microsecond duration, with a voltage sweep ranging from 500 to 1500 V amplitude. The simulations integrated an external circuit model with the magnetic transient solver. Both homogeneous and laminated core configurations were modeled to investigate the effects of conductivity and core geometry on flux diffusion and saturation. It was observed that an effective conductivity of 5 S/m yielded results reasonably consistent with experimental data. This research highlights the critical need for precise simulation of core behavior at high magnetization rates for fast pulsed power systems and sheds light on the limitations of a commercial simulation tool.